International comparison of death place for suicide; a population-level eight country death certificate study - Rhee, YongJoo; Houttekier, Dirk; MacLeod, Roderick; Wilson, Donna M; Cardenas-Turanzas, Marylou; Loucka, Martin; Aubry, Regis; Teno, Joan; Roh, Sungwon; Reinecke, Mark A; Deliens, Luc; Cohen, Joachim (Social psychiatry and psychiatric epidemiology, 2016)
PURPOSE: The places of death for people who died of suicide were compared across eight countries and socio-demographic factors associated with home suicide deaths identified. METHODS: Death certificate data were analyzed; using multivariable binary logistic regression to determine associations. RESULTS: National suicide death rates ranged from 1.4 % (Mexico) to 6.4 % (South Korea). The proportion of suicide deaths occurring at home was high, ranging from 29.9 % (South Korea) to 65.8 % (Belgium). Being older, female, widowed/separated, highly educated and living in an urban area were risk factors for home suicide. CONCLUSIONS: Home suicide deaths need specific attention in prevention programs.
Keywords: senioři; senioři nad 80 let; Death Certificates; kojenec; mladiství; International comparison; úmrtní listy; Middle Aged; mužské pohlaví; příčina smrti; Infant; sebevražda; mladý dospělý; Adult; dítě; Child; Aged, 80 and over; Child, Preschool; Young Adult; ženské pohlaví; Humans; předškolní dítě; Location of death; celosvětové zdraví; Death certificate data; lidé středního věku; Global Health; rizikové faktory; Suicide; dospělí; Female; Aged; Risk Factors; Adolescent; Cause of Death; lidé; Male